Answer:
Answer:
f(x) = - 4x + 4
Step-by-step explanation:
Step-by-step explanation:
A linear function has the form
f(x) = ax + b, thus
f(0) = a(0) + b = 4, that is
0 + b = 4 , hence b = 4
f(3) = 3a + b = - 8 ← substitute b = 4
3a + 4 = - 8 ( subtract 4 from both sides )
3a = - 12 ( divide both sides by 3 )
a = - 4, thus
f(x) = - 4x + 4
Answer:
1/-21
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
17
4
x+
−1
12
=6x
Step 2: Subtract 6x from both sides.
17
4
x+
−1
12
−6x=6x−6x
−7
4
x+
−1
12
=0
Step 3: Add 1/12 to both sides.
−7
4
x+
−1
12
+
1
12
=0+
1
12
−7
4
x=
1
12
Step 4: Multiply both sides by 4/(-7).
(
4
−7
)*(
−7
4
x)=(
4
−7
)*(
1
12
)
x=
−1
21
(3/4) /(4/5) = x/1
cross multiply
4/5x = 3/4
x = 3/4 * 5/4
x = 15/16 tons of pebbles are needed to cover the entire garden
Answer:
2/3
Step-by-step explanation:
.that's the answer
6.28 (equation for circle perimeter is 2πr)